Birleşmiş Milletler Güvenlik Konseyi’nin Reformu Sorunsalı: İtalya’nın Beklentileri ve Stratejileri - Ömer ÇOLAK; İsmail KÖSE (Gazi Akademik Bakış)
The United Nations (UN) is the most important international organization of today’s international system. Despite UN’s unchallengeable role in international relations, there is a worldwide expectation that UN will produce solid solutions towards general problems. The Security Council (UNSC), which acts as executive mechanism of the UN, is the part that is expected to receive highest share from these changes. There is no doubt that actors requesting a number of changes towards the structure of the Council are whose outside of existing permanent status of the structure. In particular, the demands for the expansion of the permanent membership quota of the group of four, consisting of Brazil, Germany, India and Japan, have encouraged their regional rivals to pursue their policies to create their group. Due to the possibility of obtaining permanent membership which of Argentina against Brazil, of Italy against Germany, of Pakistan against India and of South Korea against Japan is very low in a possible permanent membership expansion, it is seen that those states because of their incapacity trying to prevent their rivals to be permanent members. Especially Italy is one of the leading states to develop the most effective policies and reform proposals towards reforming of the UNCS. Italy’s intensive monitoring of developments in the Council’s reform process and making an intensive effort towards not stay out of a possible reform initiative is primarily due to concerns about decline of the importance of Italy’s regional equation.